Effects of fixed orthodontic appliance with antihypertensive drugs on the body weight of experimental rats - Hadeel A Mahdi; Hayder F Saloom; Muhanad A Kashmola (College of Dentistry/ University of Baghdad, 2023)
Background: This study aims to investigate the effect of fixed orthodontic appliances and/or antihypertensive drugs on the weight of experimental rats. Materials and Methods: Thir-ty-six male Wistar albino rats were subjected to a split-mouth design study, in which an orthodontic appliance was inserted in one side to move the first molar mesially for 2 weeks while the other side acted as a control to tooth movement. The rats were allocated into three groups: group A (n = 12), without any pharmacological treatment; group B (n = 12), subcu-taneous injection of bisoprolol fumarate (5 mg/kg) daily; and group C (n = 12), subcutaneous injection of valsartan (10 mg/kg) daily. A fixed orthodontic appliance with a closing coil spring delivering 50 gm of force was used to move the first molar mesially while the incisors served as an anchor unit. The weight of the rats was measured on days 1 (the day of appli-ance insertion), 7, and 14. Results: No significant (P > 0.05) difference in the body weight of rats was found among the three groups at each time point; however, significant (P < 0.05) weight loss was noted after the first and second week of the experiment in all study groups. Conclusion: The body weight loss of rats following the insertion of a fixed orthodontic ap-pliance could be related to the effects of the appliance rather than the administered antihy-pertensive drugs.